2021
DOI: 10.1093/hmg/ddab036
|View full text |Cite
|
Sign up to set email alerts
|

Dementia with Lewy bodies—associated ß-synuclein mutations V70M and P123H cause mutation-specific neuropathological lesions

Abstract: ß-Synuclein (ß-Syn) has long been considered to be an attenuator for the neuropathological effects caused by the Parkinson’s disease-related α-Synuclein (α-Syn) protein. However, recent studies demonstrated that overabundant ß-Syn can form aggregates and induce neurodegeneration in CNS neurons in vitro and in vivo, albeit at a slower pace as compared to α-Syn. Here we demonstrate that ß-Syn mutants V70M, detected in a sporadic case of Dementia with Lewy Bodies (DLB), and P123H, detected in a familial case of D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…In addition to identifying a physiological role for βSyn and γSyn, our findings may also have implications for the contributions of βSyn and γSyn to disease. βSyn and γSyn have links to several neurodegenerative diseases ( Galvin et al, 1999 , 2000 ; Nguyen et al, 2011 ; Ninkina et al, 2009 ; Nishioka et al, 2010 ; Peters et al, 2012 ; Surgucheva et al, 2002 ), and missense mutations in βSyn, as well as βSyn or γSyn overexpression, cause neurodegeneration ( Fujita et al, 2020 ; Ninkina et al, 2009 ; Ohtake et al, 2004 ; Peters et al, 2012 ; Psol et al, 2021 ; Taschenberger et al, 2013 ). We and others have previously shown that lack of SNARE chaperoning by αSyn or the CSPα chaperone complex causes progressive neuropathology ( Burré et al, 2010 , 2012 , 2015 ; Greten-Harrison et al, 2010 ; Sharma et al, 2011 , 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to identifying a physiological role for βSyn and γSyn, our findings may also have implications for the contributions of βSyn and γSyn to disease. βSyn and γSyn have links to several neurodegenerative diseases ( Galvin et al, 1999 , 2000 ; Nguyen et al, 2011 ; Ninkina et al, 2009 ; Nishioka et al, 2010 ; Peters et al, 2012 ; Surgucheva et al, 2002 ), and missense mutations in βSyn, as well as βSyn or γSyn overexpression, cause neurodegeneration ( Fujita et al, 2020 ; Ninkina et al, 2009 ; Ohtake et al, 2004 ; Peters et al, 2012 ; Psol et al, 2021 ; Taschenberger et al, 2013 ). We and others have previously shown that lack of SNARE chaperoning by αSyn or the CSPα chaperone complex causes progressive neuropathology ( Burré et al, 2010 , 2012 , 2015 ; Greten-Harrison et al, 2010 ; Sharma et al, 2011 , 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Neuron/glia co-cultures develop a fully matured neuronal network with robust intrinsic activity (Murphy et al, 1992 ), characterized as network bursts. Such cultures can be readily used to study the impact of synucleins on their network activity, in terms of frequency of network bursts and percentages of neurons contributing to network bursts (Tolo et al, 2018 ; Psol et al, 2021 ). Both parameters can be recorded with high accuracy due to the 2D-arrangement of cultured neurons, allowing to assess all cells contributing to network activity simultaneously.…”
Section: Resultsmentioning
confidence: 99%
“…Neuronal differentiation is also observed to be altered in human induced pluripotent stem cells (iPSC) derived dopaminergic neurons in the context of PD [25,26] also observed when glutamatergic neurons were transdifferentiated into dopaminergic neurons [27,28]. Mouse models of PD showed there is less amount of neurogenesis in older mice [29], as well as different protein accumulation was significantly toxic to the neurons [30]. It is, however, clear if this strategy is to be considered as a therapy approach, more work needs to be performed to determine whether adult neurogenesis is affected in neurodegenerative disorders, till then more emphasis needs to be given to identifying biomarkers to predict the disease at an earlier stage [31] or use the differentiated neurons as tools to test different drug candidates [32], as it has been demonstrated that neurons are affected differently [33].…”
Section: Discussionmentioning
confidence: 99%